A new species and key to known species of the genus Conophymacris Willemse, 1933 (Orthoptera, Acridoidea, Catantopidae, Podisminae) from China - Ye, Bao-Hua; Shen, Wei-Xing; Jia, Chun-Yan; Yin, Zhan (Zootaxa, 2021)
A new species in the genus Conophymacris Willemse, 1933 from Yunnan, China is described. The new species Conophymacris reni sp. nov. is similar to C. jiulongensis Zheng et al., 2009, but differs from latter in width of vertex between eyes of male equal to 2.8 width of frontal ridge between antennae, epiproct of male width longer than length, cercus of male apical part not wider, tegmina extending over the hind margin of first abdominal tergum, hind tibia all red, epiphallus ancorae small, lower than anterior projection, lophi not acute, width of subgenital plate shorter than its length and hind margin with 1 tooth in female. Type specimens are deposited in the Natural Museum of Hebei University, Baoding, Hebei, China.